Effect of transparent glass cover material on double slope solar still productivity. (2022) - Maheswari, K.S.; Mayandi, K.; Joe Patrick Gnanaraj, S.; Appadurai, M.
Abstract: Solar water distillation apparatus has been developed for the Thoothukudi coastal people in Tamilnadu, India, where drinking water is rare. This analysis focused on the possibility of employing stretched transparency PVC cover instead of usual clear glass sheet for solar distillation equipment. To increase the evaporative surface area, black cotton cloths with enlarged fibres were placed on the bottoms of stills. When the angle of inclination (13°) was equivalent to that of a glass sheet-covered still, more distilled water was recovered from the clear PVC sheet covered still. The solar still's collector received less sunlight than it might have because of an accumulation of water droplets sticking to the PVC lid. A plastic sheet material with reduced water surface adhesion is the ideal choice, or an anti-water surface adhesion chemical should be sought. Until this is achievable, the preferable cover material will remain traditional glass-covered solar distillation machines.